Harnessing nanotechnology for cancer treatment - Jiajun Zhu; Jiajun Zhu; HaeJu Lee; HaeJu Lee; Ruotong Huang; Ruotong Huang; Jianming Zhou; Jingjun Zhang; Xiaoyi Yang; Wenhan Zhou; Wangqing Jiang; Shuying Chen (Frontiers in Bioengineering and Biotechnology)
Nanotechnology has become a groundbreaking innovation force in cancer therapy, offering innovative solutions to the limitations of conventional treatments such as chemotherapy and radiation. By manipulating materials at the nanoscale, researchers have developed nanocarriers capable of targeted drug delivery, improving therapeutic efficacy while reducing systemic toxicity. Nanoparticles like liposomes, dendrimers, and polymeric nanomaterials have shown significant promise in delivering chemotherapeutic agents directly to tumor sites, enhancing drug bioavailability and minimizing damage to healthy tissues. In addition to drug delivery, with the utilization of tools such as quantum dots and nanosensors that enables more precise identification of cancer biomarkers, nanotechnology is also playing a pivotal role in early cancer detection and diagnosis. Furthermore, nanotechnology-based therapeutic strategies, including photothermal therapy, gene therapy and immunotherapy are offering novel ways to combat cancer by selectively targeting tumor cells and enhancing the immune response. Nevertheless, despite these progressions, obstacles still persist, particularly in the clinical translation of these technologies. Issues such as nanoparticle toxicity, biocompatibility, and the complexity of regulatory approval hinder the widespread adoption of nanomedicine in oncology. This review discusses different applications of nanotechnology in cancer therapy, highlighting its potential and the hurdles to its clinical implementation. Future research needs to concentrate on addressing these obstacles to unlock the full potential of nanotechnology in providing personalized, effective, and minimally invasive cancer treatments.